The maintenance of the subsurface chlorophyll maximum in the stratified western Irish Sea. (20th June 2013) - Williams, Charlotte; Sharples, Jonathan; Green, Mattias; Mahaffey, Claire; Rippeth, Tom
Lay Abstract: One fundamental aim of marine science is to be able to accurately quantify and predict how mixing in the ocean can affect primary production and the global carbon budget. Shelf seas are the boundary between the coastal regions and the deep ocean. They are important areas for fisheries, as well as for the absorption of carbon from the atmosphere by microscopic organisms called phytoplankton. Phytoplankton living in the well lit surface layer of temperate shelf seas (between latitudes 23.5° and 66.5°) during summer rely on the turbulent supply of nutrients to sustain their growth. By using an instrument that is able to measure fine‐scale ocean currents, we are able to quantify mixing rates in the ocean. The chemical analysis of nutrients in seawater combined with these physical measurements allowed us to quantify the turbulent supply of nutrients from the deep ocean to surface water where phytoplankton live and thus estimate the importance of various mixing mechanisms to biological processes. In the western Irish Sea, we found that, for primary production to be maintained during summer, relatively large‐scale mixing events must take place to supply the nutrients required by phytoplankton. The background mixing rate does not supply sufficient nutrients to phytoplankton, and thus storms, enhanced tidal mixing, or both are likely to be vital in sustaining primary production in this marine ecosystem. Abstract : The diapycnal flux of nitrate from the deep water provides a limit on new production in the subsurface chlorophyll maximum (SCM) during summer in stratified shelf seas. Here we estimate the diapycnal nitrate flux into the SCM in the stratified western Irish Sea (SWIS). Sampling took place immediately before neap tides when winds were light, so flux estimates reported provide a lower limit to nitrate supply to the SCM. Measurements of turbulent kinetic energy dissipation, chlorophyll a, and nitrate were used to estimate the flux of nitrate and chlorophyll through the SCM. Turbulent dissipation was low in the SCM (10 –9 to 10 –7 m 2 s –3 ), driving a correspondingly low nitrate flux into the SCM (0.31 mmol m –2 d –1 ). The thermocline was marginally stable throughout sampling, and thus the addition of shear would likely result in shear instabilities and mixing. We show that although the SWIS is documented as having an energetic internal tide at this time, there was a low level of dissipation within the thermocline. We argue that the internal tide sets up background shear, which results in marginal stability. The addition of extra shear through the passage of nonlinear internal waves and/or the wind can trigger instability and mixing. We extrapolate our flux estimate over the summer and show that the nitrate flux is insufficient to sustain the documented summer production estimates for the SWIS. This suggests that episodic events are likely to be important for nitrate fluxes, or even largely responsible for the nitrate flux that sustains the SCM.